Checklist, distribution, and a new record of Nepomorphan water bugs (Hemiptera: Heteroptera) in northern Tunisia - Slimani, Noura; Moulet, Pierre; Chen, Ping-Ping; Nieser, Nico; Pluot-Sigwalt, Dominique; Boumaïza, Moncef; Guilbert, Eric (Zootaxa, 2015)
We report on the results of a survey of the Nepomorpha of northern Tunisia, and list twenty-three species belonging to twelve genera and seven families: Nepidae, Ochteridae, Corixidae, Micronectidae, Naucoridae, Notonectidae, and Pleidae. These records are based on intensive field surveys during the year 2013 and examination of the entomological collections of the National Museum Natural History of Paris. Ranatra linearis (Linnaeus, 1758) is recorded for the first time from Tunisia. The occurrence of Sigara (Halicorixa) stagnalis stagnalis (Leach, 1817) in Tunisia is confirmed. A preliminary checklist of the Nepomorpha of Northern Tunisia and updated distribution maps for all species treated are provided for further studies.